Assessment of Sorghum Genetic Resources for Genetic Diversity and Drought Tolerance Using Molecular Markers and Agro-morphological Traits (University of Khartoum Journal of Agricultural Sciences, 2025)
Forty sorghum genotypes were investigated for geneticdiversity and drought tolerance. Diversity parameters were estimatedusing 16 Simple Sequence Repeats markers. For assessment of droughttolerance, the genotypes were field evaluated under normal and droughtstress conditions for two seasons in three environments, in Sudan. In total,98 SSRs alleles were detected with an average of 6.1 alleles per locus.The estimated polymorphic information contents ranged from 0.33 to0.86. The genetic similarity ranged from 0.00 to 0.88 with a low mean of0.32. The dendrogram, generated from the UPGMA cluster analysis,showed two main clusters differentiated into nine sub-clusters with closerelationship to morphological characters and pedigree information. Mantelstatistics revealed a good fit of the cophenetic values to the original dataset (r = 0.88). The overall mean genetic diversity was 0.67. Significantdifferences were detected among genotypes under both normal anddrought stressed conditions for all measured traits. Based on the relativeyield, the most drought-tolerant genotypes were Arfa Gadamak, WadAhmed, El-Najada, Korcola, ICSR 92003 and Sham Sham. Drought
Keywords: Genetic diversity; drought tolerance; molecular markers; morphological traits; sorghum